Konsep Rahmat Dalam Islam Perspektif Hadis Nabi Muhammad SAW. (Innamā Anā Rahmatun Muhdātun) - Rasid, Ruslan; Marhunmah, Marhumah; Rafiq, Ahmad (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2021)
Islam as the religion of Al-Salaam (salvation) highly upholds human values, one of the human values that cannot be separated from Islam is to be a figure who spreads mercy (love) to mankind regardless of background differences. There are several hadiths that point to the concept of grace and can be used as a life guide for Muslims in being religious in the midst of diversity. The purpose of this research was to analyze how the concept of grace in Islam based on the hadith of the Prophet Muhammad which reads "innamā anā rahmatun muhdātun," The research result states that the concept of mercy based on the hadith that grace in Islam was not limited to spreading compassion to anyone. But more than that, the mercy of Islam touches the joints of wider society. Islam does not invite someone to follow its teachings by force. Rahmat is also interpreted as an effort to pray for the good of others and to respect and respect all forms of differences.